Effect of pH on the denitrifying enzyme activity in pasture soils in relation to the intrinsic differences in denitrifier communities - Čuhel, Jiří (Jihočeská univerzita, 2011)
The effects of pH on denitrifying enzyme activity (DEA) and on the ratio of the denitrification products, N2O and N2, were determined in three pasture soils differing in cattle impact. The linkage between intrinsic differences in the denitrifying communities and pH effects on relative N2O production was also assessed. The soils were therefore analyzed for DEA and N2O production over a range of pH values and for the kinetic constants of NO3- and N2O reductions.
Effect of pH on the denitrifying enzyme activity in pasture soils in relation to the intrinsic differences in denitrifier communities
Keywords: denitrification; denitrifying enzyme activity; pH; soil; nitrous oxide; pasture; denitrification; denitrifying enzyme activity; pH; soil; nitrous oxide; pasture